Writing Travel as Janus: Cultural Translation as Descriptive Category for Travel Writing - Shang Wu (Interlitteraria, 2021)
Abstract: The intersection of the study of travel writing and the study of translation produces two major perspectives: travel writing in translation and translation in travel writing. The first one looks into how the travel narrative is reshaped in a different linguistic and cultural context; the other looks into the translational character of the travel narrative, as the traveller is constantly moving between languages and cultures. Though the conceptual analogy between traveller and translator has been long noted, the linguistic dimension that marks the language difference in travel narrative is rarely underlined. In this essay, in order to explore the possibility of foregrounding both the conceptual link between travel and translation and the linguistic dimension of travel narrative, I propose to integrate an attention to language difference into a reinvention of the contested yet promising term ‘cultural translation’. The American writer Peter Hessler’s travel account Country Driving is cited as a case study.